How Is Diversity Represented in Basketball Organizations Active in the Romanian National Basketball League - Vlad BRANGA (Journal of Emerging Trends in Marketing and Management, 2023)
For years, globalization has been a topic of interest for researchers and basketball organizations alike. Because of globalization, basketball organizations are able to access a wider market for basketball players and can thus choose the most suited for their teams. However, this can also be seen as a challenge for basketball organizations as they need to take into consideration managing diversity in their teams. Considering this, the aim of this paper is to provide an insight into how diversity is represented in the Romanian National Basketball League during the 2022-2023 season. The research question for this paper is “How is diversity being considered by the Romanian Basketball Federation and Basketball Organizations active in the men’s senior division?” The method used for this paper is a literature review together with an analysis on the specific data that was gathered by the author from various sources. The results show that countries like USA and Serbia are the source for the majority of the foreign players in the league while many other countries have 1-2 players representing them. However, in regards to gender differences in basketball organizations, there are very few women hired at basketball organizations active in the Romanian National Basketball League during the 2022-2023 season. Moreover, future and more detailed qualitative or quantitative research having as target group: presidents of the basketball organizations could be conducted for more in depth analyses on how they manage diversity in their organizations.